Electric Motor Efficiency: A Key Pillar in Tackling Air Pollution - Nurul Fadhilah (Oshada, 2024)
In the face of serious threats of air pollution from conventional motor vehicles, electric motors are emerging as a key pillar in the effort to achieve clean air and optimal health. This article explores the concept of electric motor efficiency and its crucial role in addressing air pollution that can impact health. Electric motors not only eliminate exhaust emissions, but also offer higher energy conversion efficiency, reducing energy losses during their movement. By referring to reputable sources such as the International Energy Agency (IEA) and the American Council for an Energy-Efficient Economy (ACEEE), we can understand the positive impact electric motors have on air quality. While some challenges such as battery range limitations need to be overcome, the efficiency of electric motors remains the key to paving the way towards sustainable solutions to significantly reduce the impact of air pollution. Air pollution has serious impacts on human health. Both long-term and short-term exposure to air pollutants can cause a variety of serious health problems such as respiratory tract disorders cardiovascular diseases and others.